Epidemiological characterization, contraception and psychological well-being in women two years after therapeutic abortion - Guevara Ríos, Enrique (2021)
Objective: To describe the epidemiological characteristics, contraception and psychological well-being in a series of women two years after therapeutic abortion. Materials and methods: Observational, descriptive study of a series of cases. The women whose therapeutic abortion procedure was performed at the National Maternal Perinatal Institute of Peru in 2018 participated and who at the time of the interview had passed two years, with prior informed consent. Sociodemographic data, obstetric profile, family planning method before therapeutic abortion and current were collected. The BIEPS Scale was applied to measure the psychological well-being of the participants two years after therapeutic abortion. Descriptive analysis was carried out and the identity of the participants was safeguarded. Results: 12 women were studied two years after presenting therapeutic abortion. At the time of the therapeutic abortion, they were between 21 and 38 years old, the gestational age was between 14 and 22 weeks, of the 12 cases, five women did not use contraception. All cases presented fetal pathology, being more frequent hydrops fetalis and cystic hygroma. All the women had altered mental health. The most frequent abortion procedure used was the use of misoprostol and uterine curettage, in 11 cases. After the therapeutic abortion, 7 out of 12 did not use any method, 5 women had a high degree of psychological well-being and 7 a high level. In the evaluated domains of psychological well-being, the highest scores were in purpose in life (11 cases out of 12), followed by self-acceptance (10 cases out of 12) and personal growth (3 cases out of 12). While, the domains with a mean score were positive relationships, autonomy and domain of the environment. Conclusions: These findings suggest that women with a pregnancy with a fetus with congenital malformations incompatible with life presented an alteration in their mental health. Under these conditions, the women presented a therapeutic interruption of their pregnancy; and after two years they presented adequate psychological well-being.